Seasonal patterns of activity, travel and water intake for livestock in south Turkana, Kenya - Coppock, D. Layne; Ellis, J.E.; Swift, D.M. (1988)
Reports on how seasonal change influences various management tactics, time budgets, travel distances and water intakes of livestock during one annual cycle.